2016
DOI: 10.2147/cia.s103605
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain after percutaneous coronary intervention in patients with stable angina

Abstract: BackgroundPercutaneous coronary intervention (PCI) has been widely used to treat acute coronary syndrome but is only recommended as an additional treatment to medical therapy and risk modification in patients with refractory or progressing angina. The number of PCI in this patient population is still increasing. Post-PCI chest pain (PPCP) is one of the common problems of PCI. Its presentation and causes in patients with stable angina are poorly understood.Patients and methodsThis study retrospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
8
3
1
Order By: Relevance
“…Despite advances in medical and interventional treatments, many patients develop recurrent angina pectoris without coronary artery stenosis following complete coronary revascularization at initial PCI. [19] In the present study, 53.5% of patients developed recurrent angina pectoris following PCI without revascularization at one-year followup.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Despite advances in medical and interventional treatments, many patients develop recurrent angina pectoris without coronary artery stenosis following complete coronary revascularization at initial PCI. [19] In the present study, 53.5% of patients developed recurrent angina pectoris following PCI without revascularization at one-year followup.…”
Section: Discussionmentioning
confidence: 43%
“…In recent studies, an elevated BMI [20] and a higher number of stents [19] increased the risk of developing recurrent angina pectoris after PCI, whereas the administration of nicorandil reduced the risk. [21] The current study is consistent with this report as we found that an elevated BMI correlated with a higher TIMI frame count.…”
Section: Discussionmentioning
confidence: 99%
“…Chest pain after PCI may be experienced in 36% to 42% of patients undergoing both elective and emergent PCI 15‐17 . It is most commonly described in the first 24 h following PCI but is described as occurring within the first 3 weeks 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A high rate of post-PCI chest pain is also recorded in patients with stable CAD. In a study which included 167 patients who underwent elective PCI for stable CAD, Chang et al reported an incidence of 41.9% of post-PCI chest pain 53.…”
mentioning
confidence: 99%